Bioseparations science and engineering - Harrison, Roger G., 1944-; Todd, Paul, 1936-; Rudge, Scott R.; Petrides, Demetri P. (Topics in chemical engineering., 2015)
Designed for undergraduates, graduate students, and industry practitioners, Bioseparations Science and Engineering fills a critical need in the field of bioseparations. Current, comprehensive, and concise, it covers bioseparations unit operations in unprecedented depth. In each of the chapters, the authors use a consistent method of explaining unit operations, starting with a qualitative description noting the significance and general application of the unit operation. They then illustrate the scientific application of the operation, develop the required mathematical theory, and finally, descr.